A dyad approach to understanding relationship satisfaction and health outcomes in military couples following service member and veteran traumatic brain injury - Brickell, Tracey A.; Ivins, Brian J.; Wright, Megan M.; Sullivan, Jamie K.; French, Louis M.; Lange, Rael T. (Frontiers in Psychiatry, 2025)
ObjectiveUsing a dyadic approach, this study examined health and family outcomes in military couples following service member and veteran (SMV) traumatic brain injury (TBI), within the context of relationship satisfaction.MethodsParticipants included 164 dyads (N = 328), composed of US SMVs (n = 164) and their intimate partners (IPs, n = 164). Dyads completed a measure of relationship satisfaction, as well as measures of psychological, social, caregiving, family, neurobehavioral, and/or PTSD outcomes. Dyads were classified into four relationship satisfaction groups: (1) SMV and IP satisfied (Both Satisfied, n = 72 dyads), (2) SMV satisfied and IP dissatisfied (SMVsat/IPdis, n = 25 dyads), (3) SMV dissatisfied and IP satisfied (SMVdis/IPsat, n = 21 dyads), and (4) SMV and IP dissatisfied (Both Dissatisfied, n = 46 dyads).ResultsWithin dyads, SMVs reported worse scores than their IPs, except in the SMVsat/IPdis group, where their dissatisfied IPs reported worse scores on four measures. Across groups, dissatisfied SMVs reported worse scores compared to satisfied SMVs, and dissatisfied IPs reported worse scores compared to satisfied IPs. Satisfied and dissatisfied SMVs and IPs in the mixed relationship satisfaction groups reported little to no differences across measures compared to their respective SMVs and IPs in the Both Satisfied and Both Dissatisfied groups, with the exception of the family measures for dissatisfied SMVs or IPs.ConclusionsRelationship dissatisfaction was related to worse health and family outcomes, even when the other members of the dyad reported satisfaction in their relationship. A dual-goal, dyadic approach to TBI treatment that focuses on how individual, couple, and family factors interact will likely maximize service member recovery and return to duty, as well as outcomes for military families.